2017
DOI: 10.1093/jxb/erx076
|View full text |Cite
|
Sign up to set email alerts
|

Amylases StAmy23, StBAM1 and StBAM9 regulate cold-induced sweetening of potato tubers in distinct ways

Abstract: HighlightStAmy23, StBAM1 and StBAM9 play distinct roles in potato cold-induced sweetening by preferentially acting on soluble phytoglycogen, soluble starch and starch granules, respectively, in different subcellular locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 57 publications
0
55
1
6
Order By: Relevance
“…Only expression of the alpha‐amylase 23 ( StAmy23 ) increased about 2.5‐fold under heat conditions (Figure d) which may together with the overall lower expression of starch biosynthesis genes account for the reduced accumulation of transitory starch. StAmy23 localizes in the cytoplasm and was suggested to play a role in the degradation of cytosolic phytoglycogen (Hou et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only expression of the alpha‐amylase 23 ( StAmy23 ) increased about 2.5‐fold under heat conditions (Figure d) which may together with the overall lower expression of starch biosynthesis genes account for the reduced accumulation of transitory starch. StAmy23 localizes in the cytoplasm and was suggested to play a role in the degradation of cytosolic phytoglycogen (Hou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the accumulation of transitory starch was clearly decreased in leaves grown under heat conditions (Figure 3c), expression profiles of starch genes as described by Van Harsselaar, Lorenz, Senning, Sonnewald, and Sonnewald (2017) were analysed (Table S7) (Hou et al, 2017).…”
Section: Naked Pinsmentioning
confidence: 99%
“…Our previous research demonstrated that genes involved in starch degradation and sucrose cleavage were differentially expressed between CIS‐resistant and CIS‐sensitive potato genotypes upon exposing to low temperature (Chen et al, ). Further studies confirmed that regulating starch hydrolysis (Hou et al, ; Zhang et al, ) and sucrose cleavage (Lin et al, ; Liu et al, ) impacted on potato CIS and chip color. We also detected abundant expression of the genes involved in glycolysis and speculated that potato CIS may be synergistically controlled by different metabolic pathways (Chen et al, ).…”
Section: Introductionmentioning
confidence: 80%
“…Starch is metabolized to reducing sugars by a series of enzymes catalyzing the reactions of starch breakdown and hexogenesis. Several studies have demonstrated the implication of these processes in CIS 1620 . However, the amount of reducing sugars generated in the potato tubers is the function of a synergistic action of the enzymes catalyzing the afore-mentioned processes and the interrelated pathways of starch synthesis, glycolysis, and respiration 13,21 .…”
Section: Introductionmentioning
confidence: 99%